2023
DOI: 10.1371/journal.pone.0293410
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing trend of blood lipid profile in type 2 diabetes: Not a promising change in HDL-C, a serial cross-sectional study

Amirhossein Yadegar,
Fatemeh Mohammadi,
Soghra Rabizadeh
et al.

Abstract: Background The prevalence of dyslipidemia in patients with type 2 diabetes (T2D) has been reported to be relatively high. The current study aimed to investigate the trend of serum lipid levels and the prevalence of dyslipidemia in patients with T2D. Methods Data were extracted from a cohort of patients with T2D who had regular follow-ups every year for three years. TG, TC, LDL-C, HDL-C, and non-HDL-C were analyzed. The atherogenic index of plasma (AIP) was calculated using log (TG/HDL-C). Results A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Diabetes is an independent risk factor for CVD [ 7 ]. CVD risk factors such as dyslipidemia, hypertension, obesity, and autonomic dysfunction are also more prevalent in patients with diabetes [ 8 , 9 ]. Timely diagnosis of CVD in patients with diabetes faces challenges due to altered or obscured typical CVD symptoms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is an independent risk factor for CVD [ 7 ]. CVD risk factors such as dyslipidemia, hypertension, obesity, and autonomic dysfunction are also more prevalent in patients with diabetes [ 8 , 9 ]. Timely diagnosis of CVD in patients with diabetes faces challenges due to altered or obscured typical CVD symptoms [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis development could be protected through different HDL-C capacities, including cholesterol removal from the artery wall, vasodilation in endothelial cells, protective effects on low-density lipoprotein (LDL) oxidation, and anti-inflammatory effects[ 9 , 18 ]. To date, there is a lack of documented conclusive evidence for the effectiveness of HDL-C-raising drugs [ 9 , 19 , 20 ]. Although it has been shown that niacin and cholesterol ester transfer protein (CETP) inhibitors could lead to an increase in HDL-C levels, the cardiovascular risk was not substantially reduced using such medications [ 5 ].…”
Section: Introductionmentioning
confidence: 99%